Penerapan Metode Kompresi Burrows Wheler Transform Pada Citra Hasil Interpolasi Bicubic - Sarmiyana Purba (JURIKOM (Jurnal Riset Komputer), 2019)
Image compression or image compression aims to minimize memory requirements in representing digital images by reducing duplication of data in the image so that the memory needed is less than the original image representation. This is useful to shorten the image sending time and also save memory usage compared to uncompressed images. One image that is often compressed is the image of interpolation. Interpolation (often called resampling) is an imaging method to increase (or reduce) the number of pixels in a digital image. Some digital cameras use interpolation to produce images that are larger than the captured sensor or to make digital zoom. Almost all image editing software supports one or more interpolation methods. How an enlarged image can be smooth without leaving the impression of rupture depends very much on the sophistication of the interpolation algorithm. Burrows Wheler Transform Algorithm and Bicubic Interpolation Algorithm are good compression and interpolation methods in image processing. Magnification and compression of the image of an image is done by performing matrix operations on the image to be enlarged and compressed